COMMUNICATIVE DIFFICULTIES IN ENGLISH AND WAYS TO OVERCOME THEM - Zarina, Isakhanova (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY RESEARCH AND INNOVATIVE TECHNOLOGIES, 2021)
Communication in an organizational context involves interactions between people. Internal communications play a special role in group dynamics. Without communication, there is no communication, no exchange of information, and there can be no group without a bus.